2021
DOI: 10.3390/children8111034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum and Salivary Iron and Ferritin Levels in Children with Dental Caries: A Meta-Analysis and Trial Sequential Analysis

Abstract: Background and objective: Dental caries appears to be related to iron deficiency anemia and to low ferritin levels. In the present meta-analysis, we report salivary and serum iron and ferritin levels in children with dental caries, compared to healthy controls. Materials and methods: We searched in Web of Science, Cochrane Library, Scopus, and PubMed/Medline databases to extract studies published until 25 July 2021. We calculated mean differences (MD) and 95% confidence intervals (CI) of salivary and serum iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The network-based visualization approach also identi ed cotinine as moderately correlated to the blood cadmium in the high lead caries subset, con rming previous studies showing the association of serum cotinine, cadmium, and caries extending the association to include the lead caries subset [13,24,25]. This approach also identi ed a moderately and highly correlated frozen serum iron hemoglobin, hemoglobin transferrin saturation and hemoglobin red cell distribution width and hematocrit in the high lead caries population.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The network-based visualization approach also identi ed cotinine as moderately correlated to the blood cadmium in the high lead caries subset, con rming previous studies showing the association of serum cotinine, cadmium, and caries extending the association to include the lead caries subset [13,24,25]. This approach also identi ed a moderately and highly correlated frozen serum iron hemoglobin, hemoglobin transferrin saturation and hemoglobin red cell distribution width and hematocrit in the high lead caries population.…”
Section: Discussionsupporting
confidence: 79%
“…Non-ordinal categorical variables were encoded with one hot encoding technique (by creating a dummy variable for each categorical value). Speci c variables, such as serum iron and lead concentration, dietary sugar, number and severity of tooth decay were included based on existing literature and applicability to the study criteria [12][13][14]. The list of selected variables is outlined in the Table S1.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Another study [55] that included 53 genes reported as being involved in DC susceptibility showed that cytokine network relevant genes, the transforming growth factor-beta family, and the matrix metalloproteinases family had important roles in tooth development and carious lesions. It is believed that the flow of saliva, pH, and chemical composition of saliva are among other important factors in the occurrence and progress of DC [56][57][58]. The present meta-analysis reported that ethnicity and type of dentition were important factors for the relationship of DEFB1 rs11362 polymorphism with susceptibility to DC in children.…”
Section: Discussionmentioning
confidence: 55%
“…Dental caries are among of the most prevalent dental diseases in children [20]. Increasing evidence has demonstrated that ID is closely associated with ECC [9,21]. In this study, we explored the effects of iron levels on the pathological charac-teristics of dental caries in a rat model.…”
Section: Discussionmentioning
confidence: 99%